Enhancing MSME Financial Performance through Accounting Knowledge, Work Motivation, and Business Scale: Penelitian - Fitri Wahyuni; Annisa Ulfah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of accounting knowledge, work motivation, and business scale on the use of accounting information in enhancing the financial performance of Micro, Small, and Medium Enterprises (MSMEs). MSMEs contribute significantly to the national economy but continue to face various challenges in financial management, particularly in utilizing relevant accounting information. The research was conducted among MSME actors in Sleman Regency using a quantitative approach. The sampling technique employed was convenience sampling, involving 100 respondents. The research instrument used was a questionnaire, and the data were analyzed using the Partial Least Squares (PLS) method. The results indicate that accounting knowledge and work motivation have a positive and significant effect on the use of accounting information, while business scale shows a positive but not significant effect. These findings affirm that entrepreneurs’ understanding of accounting and their internal motivation are key factors in improving the use of accounting information, which ultimately can strengthen the financial performance of MSMEs. Therefore, continuous policy support, training, and mentoring programs are necessary to enhance financial literacy and improve the competitiveness of MSMEs in an increasingly challenging market environment.